Inovasi Teknologi Tepat Guna: Implementasi Mesin Penyuir Daging Bebek Pada Industri Kecil Menengah (IKM) Pangan Lokal - Sihombing, Rolando; Sitopu, Joni Wilson; Saragih, Andika Maranatha; Hidayah, Mhd. Qory; Hernanda, Yogi (Yayasan Kajian Riset Dan Pengembangan Radisi, 2023)
Small and medium-sized meat processing industries (SMEs) face challenges in shredding duck meat, which has dense and coarse muscle fibers. This Community Service project aims to design a shredding machine based on a pulley transmission that is efficient, hygienic, and meets the needs of SMEs. The method used is Community Service engineering (R&D) with a prototype design approach, performance testing, and analysis of power consumption and shredded results. Data was obtained through direct observation and testing in Marihat Jaya Village in Pematangsiantar City. The results show that the machine is capable of shredding up to 5 kg/minute with a power consumption of 1.3 kW and producing uniform shreds. This machine has proven to be effective, safe, and worthy of being developed as an appropriate technology for local food SMEs.